EFFECT OF PERIWINKLE (CATHARANTHUS ROSEUS) LEAF EXTRACT ON LIVER HISTOLOGY OF MICE (MUS MUSCULUS L) AFTER ASPARTAME INDUCE - Mahriani Mahriani; Rosita Dewi Wulandari; Susantin Fajariyah (Universitas Medan Area, 2022)
Aspartame is an artificial sweetener in foods and beverages. Continuous use of aspartame will result in oxidative stress in the liver. So we need antioxidants from outside the body such as periwinkle leaves.This study aims to determine the effect of periwinkle leaves (Catharanthus roseus L) on aspartame-induced liver histology. This study used 24 male mice divided into 4 groups, namely negative control (K-) without treatment; Positive control (K +) treatment of aspartame; D1: treatment of aspartame and periwinkle extract doses of 0.42 mg/kg. D2: aspartame and periwinkle extract doses of 0.84 mg/kgbb. Administration of aspartame dose of 0.2 mg /kgbb by intraperitoneal for 14 days followed by gavage administration of periwinkle leaf extract for 12 days. The liver was taken on the 27th day by surgery, then made slide histology with Hematoxylin-Eosin staining. The results show that the administration of Catharanthus roseus leaf extract at a dose of 0.84 mg/kgbw in aspartame-induced mice was effective in reducing hepatocyte damage, namely hydrophilic degeneration and necrosis.